The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1007/s10295-010-0775-9
|View full text |Cite
|
Sign up to set email alerts
|

A new tool to detect high viscous exopolymers from microalgae

Abstract: Microalgae are microorganisms often surrounded by a slime layer made of secreted polymeric substances sometimes including polysaccharides. These polysaccharides, weakly described in the literature, can constitute value-added molecules in several industrial areas. The aim of this article is to show that a new tool, the BioFilm Ring Test®, can be used to detect viscous microalgal exopolymers. Two red microalgal strains (Rhodella violacea and Porphyridium purpureum), one cyanobacterium (Arthrospira platensis) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…Cations (calcium, magnesium, manganese) interfered with the behavior of the beads in the BFRT ® and decreased the BFI. Similar artefactual interactions have also been described with pronase [37] or with culture media with high ionic strength [38]. Such interaction has also been observed with antimicrobial cationic peptides derived from cathelicidin and which, at neutral pH, have many positive charges (C. Nagant, personal communication).…”
Section: Discussionsupporting
confidence: 59%
“…Cations (calcium, magnesium, manganese) interfered with the behavior of the beads in the BFRT ® and decreased the BFI. Similar artefactual interactions have also been described with pronase [37] or with culture media with high ionic strength [38]. Such interaction has also been observed with antimicrobial cationic peptides derived from cathelicidin and which, at neutral pH, have many positive charges (C. Nagant, personal communication).…”
Section: Discussionsupporting
confidence: 59%
“…epidermidis and Staph. aureus aureus (Chavant et al 2007;Badel et al 2008Badel et al , 2011a. BRT is a powerful analytical tool that enables quick and convenient screening of anti-biofilm agents based on the mobility of magnetic beads in the bacterial culture medium.…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that hydrocolloid solutions of sPS, produced by red microalgae and the cyanobacterium A. platensis , present a non-Newtonian behaviour, as their viscosity depends negatively on the shear strain rate, i.e. , decreases with the increase of this last parameter [50,72,75,81,84,85], thus showing that it is a pseudoplastic compound [86] with a strong shear-thinning behaviour [75]. However, Sun et al [58] showed that fragments of EPS from Porphyridium had a different rheological behaviour, depending on the degree of degradation, sometimes exhibiting typical characteristics of Newtonian fluids.…”
Section: The Polysaccharides From Marine Microalgae: From the Sourmentioning
confidence: 99%